2006
DOI: 10.1159/000092958
|View full text |Cite
|
Sign up to set email alerts
|

Microbleeds in Alzheimer Disease Are More Related to Cerebral Amyloid Angiopathy than Cerebrovascular Disease

Abstract: Cerebral amyloid angiopathy (CAA) is one of the cardinal pathological features in the vascular components of Alzheimer’s disease (AD). CAA itself results in disrupted microvasculature, mainly in the cerebral cortex, eventually leading to a brain cortical or subcortical hemorrhage in a population of elderly people, but clinically overt brain hemorrhages are not so frequent in AD patients. Here we assessed 50 AD patients and 26 controls to detect latent brain hemorrhages with gradient-echo T2*-weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 26 publications
(25 reference statements)
5
65
2
2
Order By: Relevance
“…In healthy subjects or patients with subjective complaints, the prevalence of SHF depicted on 2D T2*-weighted gradient recalled-echo images ranged from 0% to 21%. 14,23,24 It ranged from 18% to 32% in AD 22,25 and from 65% to 85% in VaD 22,26 ; in patients with MCI, it was reported to be 20%. 22 On a 1.5T SWI study by Goos et al, 28 the prevalence of SHF was 30% in subjective complaints, 39% in AD, and 44% in MCI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In healthy subjects or patients with subjective complaints, the prevalence of SHF depicted on 2D T2*-weighted gradient recalled-echo images ranged from 0% to 21%. 14,23,24 It ranged from 18% to 32% in AD 22,25 and from 65% to 85% in VaD 22,26 ; in patients with MCI, it was reported to be 20%. 22 On a 1.5T SWI study by Goos et al, 28 the prevalence of SHF was 30% in subjective complaints, 39% in AD, and 44% in MCI.…”
Section: Discussionmentioning
confidence: 99%
“…42 Among the neurodegenerative dementia groups, the order of the prevalence of ␤-amyloid binding was similar to that of the relative prevalence of SHF in our study. On the basis of neuropathologic studies, 23,43 microbleeds are frequently observed in the brains of patients with AD and are mainly related to ␤-amyloid pathology (cerebral amyloid angiopathy). Moreover, a neuropathologic study showed a relatively high prevalence of ␤-amyloid pathology and cortical microhemorrhages in the brains of patients with DLB 27,44 and a low prevalence of ␤-amyloid pathology in patients with FTLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alzheimer disease, for instance, is reported to have a CMB prevalence of 18%-32% versus 3%-11% in healthy populations imaged with MR field strengths of 1T-1.5T. [6][7][8][9][10][11][12][13][14][15] Consequently, CMBs are hypothesized to play an important role in the disease mechanisms of dementia as well as being a marker of the synergistic effects between vascular and amyloid pathology. 16 Of further interest, CAA and hypertension are the most common causes of intracerebral hemorrhage, with CMBs being proposed as a possible predictor of intracerebral hemorrhage.…”
mentioning
confidence: 99%